Exploring the link between top‐down information sharing and organisational performance: the moderating role of flexible manufacturing strategy. (21st February 2017) - Park, Rhokeun
Abstract : This study examines whether organisational citizenship behaviour (OCB) mediates the relationship between information sharing and organisational performance. The independent role of information sharing in employee outcomes and organisational performance has been largely overlooked in the HRM literature. Although information sharing can contribute to organisational performance through various processes, the field reveals little regarding the mechanisms of how information sharing may lead to organisational performance. This study also investigates the moderating role of flexible manufacturing strategy in the relationship between information sharing and OCB. The study found that OCB plays a role as a mediator in the relationship between information sharing and organisational performance. The relationship between information sharing and OCB was stronger in firms with a flexible manufacturing strategy than in firms with a mass production strategy. The findings provide implications on how information sharing is related to organisational performance and which organisations should share more information with their employees.